Distributed Steganography in PDF Files—Secrets Hidden in Modified Pages - Katarzyna Koptyra; Marek R. Ogiela (Entropy, 2020)
This paper shows how to diffuse a message and hide it in multiple PDF files. Presented method uses dereferenced objects and secret splitting or sharing algorithms. It is applicable to various types of PDF files, including text documents, presentations, scanned images etc. Because hiding process is based on structure manipulation, the solution may be easily combined with content-dependent steganographic techniques. The hidden pages are not visible in typical application usage, which was tested with seven different programs.